Sampling on the incidence of cervical neoplastic disease in Lima - Castillo Jessen, María (2015)
It is recommended for better correlation in cytologic and histologic diagnoses group the different forms of cervical neoplastic disease between categories: a) moderate mild dysplasia. b) severe dysplasia carcinoma in-situ c) Infiltrating carcinoma. An analysis of the incidence and age distribution of cervical neoplastic disease in 3,000 women undergoing cervical-vaginal cytology is made. The findings show an average age and a matching distribution as observed in other countries, reaffirming the potentially progressive nature of atypical minor injuries. Draws attention to the younger average age of invasive cervical carcinoma in Lima in relation to that observed in other countries.